2022
DOI: 10.3390/rs15010169
|View full text |Cite
|
Sign up to set email alerts
|

Influence of DEM Resolution on the Hydrological Responses of a Terraced Catchment: An Exploratory Modelling Approach

Abstract: Terracing is widely used as an effective soil and water conservation practice in sloped terrains. Physically based hydrological models are useful tools for understanding the hydrological response of terraced catchments. These models typically require a DEM as input data, whose resolution is likely to influence the model accuracy. The main objective of the present work was to investigate how DEM resolution affects the accuracy of terrain representations and consequently the performance of SWAT hydrological mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The field Ksat data collection did not include subsurface soil Ksat values. Ksat may vary with soil depth, and this omission could potentially affect model predictions, as more observed data might enhance the model performance and reduce model simulation uncertainty [20,25,31,69,79]. In addition, this study showed that 1 m DEM could provide a more detailed and accurate analysis in this study relative to coarser DEMs.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 81%
See 1 more Smart Citation
“…The field Ksat data collection did not include subsurface soil Ksat values. Ksat may vary with soil depth, and this omission could potentially affect model predictions, as more observed data might enhance the model performance and reduce model simulation uncertainty [20,25,31,69,79]. In addition, this study showed that 1 m DEM could provide a more detailed and accurate analysis in this study relative to coarser DEMs.…”
Section: Study Limitations and Future Directionsmentioning
confidence: 81%
“…Higher-resolution digital elevation models (DEMs) may result in similar findings. Rocha et al [31] used the SWAT model with different DEM resolutions (from 0.25 m to 10 m) to simulate streamflow. Results indicated that at 10 m resolution, the DEM generated streamflow hydrographs closer to observed records.…”
Section: Introductionmentioning
confidence: 99%
“…LiDAR data are also used in combination with other products to analyze the terrain. The authors in [30] investigated how DEM resolution affects the accuracy of terrain representations and consequently the performance of the SWAT hydrological model in simulating streamflow for a terraced eucalypt-dominated catchment (Portugal). For this research, multi-resolution DEMs (10 m, 1 m, 0.5 m, 0.25 m, and 0.10 m) based on photogrammetric techniques and LiDAR data were used.…”
Section: State Of the Art Of Methodologies For Implementation Of E-busesmentioning
confidence: 99%
“…For that, it must be managed and quantified by the implementation of tools that could help decision-support and management processes. Among these tools, hydrological models have emerged over the last thirty years [1][2][3][4][5][6][7], particularly models of rainfall-runoff transformation, recharge, and evaporation [8][9][10]. The primary focus of hydrological modeling is to reproduce the flows with the smallest possible error.…”
Section: Introductionmentioning
confidence: 99%